2021
DOI: 10.3390/molecules26092421
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Triazolopyrazine Antimalarial Compounds

Abstract: A radical approach to late-stage functionalization using photoredox and Diversinate™ chemistry on the Open Source Malaria (OSM) triazolopyrazine scaffold (Series 4) resulted in the synthesis of 12 new analogues, which were characterized by NMR, UV, and MS data analysis. The structures of four triazolopyrazines were confirmed by X-ray crystal structure analysis. Several minor and unexpected side products were generated during these studies, including two resulting from a possible disproportionation reaction. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…In addition, consistent with reported SAR data [14,16,21], the ether-linked compounds 4-6 exhibited strong activity with IC 50 values of 0.2-1.2 µM, whereas compounds 7-9 with the removal of the phenyl ring from the ether methylene group resulted in a loss of potency at the tested concentrations. For fluorinated compounds, previous studies [14] reported that the introduction of CF 3 and CF 2 Me groups at the C-8 position of scaffold 2 improved the antimalarial activity. In particular, compounds with a CF 2 Me moiety showed a 7.3-fold improvement in potency (IC 50 = 1.7 µM) compared to the parent scaffold 2 (IC 50 = 12.6 µM) [14].…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…In addition, consistent with reported SAR data [14,16,21], the ether-linked compounds 4-6 exhibited strong activity with IC 50 values of 0.2-1.2 µM, whereas compounds 7-9 with the removal of the phenyl ring from the ether methylene group resulted in a loss of potency at the tested concentrations. For fluorinated compounds, previous studies [14] reported that the introduction of CF 3 and CF 2 Me groups at the C-8 position of scaffold 2 improved the antimalarial activity. In particular, compounds with a CF 2 Me moiety showed a 7.3-fold improvement in potency (IC 50 = 1.7 µM) compared to the parent scaffold 2 (IC 50 = 12.6 µM) [14].…”
Section: Resultssupporting
confidence: 89%
“…Previous structure–activity relationship (SAR) studies reported that any substitution at the C8 position of Series 4 triazolopyrazines can lower the potency for P. falciparum [ 14 16 ]. However, a recent preliminary SAR study identified that substitution at the C8 position with trifluoromethane and difluoroethane moieties using Diversinate™ chemistry increased the potency of the parent scaffold (compound 2 ), suggesting the potential of these fluoroalkyl groups for improving the potency of other promising leads within the OSM project [ 14 ]. Fluorine-containing compounds have exhibited wide applications in pharmaceuticals and agrochemicals – approximately 20% of marketed drugs are fluoro-pharmaceuticals, while for agrochemicals, 53% are fluoro-compounds [ 17 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations